Taguchi method to determine the best location for cooling and heating appliances. Issue 4 (21st October 2019) - Pezeshki, Zahra; Soleimani, Ali; Darabi, Ahmad
Abstract : Today, saving energy is very important. Plenty of research has tried to minimise energy losses. The first step for maintaining energy is to find a way to reduce consumption and save money, which means less cost, fuel and pollution. Hence, there is a need to look for the necessary infrastructure to reduce the use of and distribute optimal energy. In this paper, the Taguchi method for energy modelling (EM) optimisation is proposed to predict the best location for heating and cooling appliances. Here, all information about one of the units of the Toos Arman Star Apartment Hotel located in Mashhad, Iran, was obtained. Based on fundamental analysis, the major factors are building coordinates ( X, Y, and Z ). According to the major factors, orthogonal array L25 is engaged for Taguchi experiments. The authors tried to maximise the satisfaction of building residents by defining the fitness function approaching to thermal comfort point of 25°C. Based on L25 of Taguchi experiments, the best successful result is analysed to select the level of major factors. The result of Taguchi optimisation was introduced into Comsol Multiphysics software and EM was performed using the determined critical points again. The experimental results show the successful location for cooling and heating appliances compared to the initial design of room 1.